“Planeterranea”: An attempt to broaden the beneficial effects of the Mediterranean diet worldwide - Vetrani, Claudia; Piscitelli, Prisco; Muscogiuri, Giovanna; Barrea, Luigi; Laudisio, Daniela; Graziadio, Chiara; Marino, Francesca; Colao, Annamaria (Frontiers in Nutrition, 2022)
Non-communicable diseases (NCDs) lead to a dramatic burden on morbidity and mortality worldwide. Diet is a modifiable risk factor for NCDs, with Mediterranean Diet (MD) being one of the most effective dietary strategies to reduce diabetes, cardiovascular diseases, and cancer. Nevertheless, MD transferability to non-Mediterranean is challenging and requires a shared path between the scientific community and stakeholders. Therefore, the UNESCO Chair on Health Education and Sustainable Development is fostering a research project – “Planeterranea” – aiming to identify a healthy dietary pattern based on food products available in the different areas of the world with the nutritional properties of MD. This review aimed to collect information about eating habits and native crops in 5 macro-areas (North America, Latin America, Africa, Asia, and Australia). The information was used to develop specific “nutritional pyramids” based on the foods available in the macro-areas presenting the same nutritional properties and health benefits of MD.